Fetal Cerebral Artery Mitochondrion as Target of Prenatal Alcohol Exposure - Bukiya, Anna N. (Int J Environ Res Public Health, 2019)
Prenatal alcohol exposure results in an array of developmental abnormalities known as fetal alcohol spectrum disorders (FASDs). Despite the high prevalence of FASDs, therapeutic interventions against accidental or intended exposure of developing fetuses to alcohol are limited. This review outlines current knowledge about mitochondria in cerebral blood vessels as a potential target for anti-FASDs intervention. First, it describes the multifaceted role of mitochondria in maintaining the cerebral artery diameter as shown in adult tissue. Second, current literature on alcohol-driven damage of mitochondrial morphology and function in several fetal tissues, including liver, heart, and brain is summarized. The functional consequences of alcohol exposure in these organs include morphological enlargement of mitochondria, increased oxidative stress, and alteration of cellular respiration. These studies point to a tissue-specific effect of alcohol on mitochondrial function and a particular vulnerability of fetal mitochondria to alcohol exposure when compared to adult counterparts. Third, recent work from our group describing persistent changes in fetal baboon cerebral artery proteome following three episodes of prenatal alcohol exposure is reviewed. In conclusion, the consequences of prenatal alcohol exposure on cerebral artery mitochondria constitute an open field of investigation and, eventually, a point of therapeutic intervention against FASDs.